2017
DOI: 10.1002/adem.201700139
|View full text |Cite
|
Sign up to set email alerts
|

Study of Interfacial Interactions in Physically Transient Soft Layered Structures: A Step toward Understanding Interfacial Bonding and Failure in Soft Degradable Structures

Abstract: Soft multilayer structures have broad applications in transient electronics. Strain-mismatch-induced fracture is key in achieving physical transiency. Here, swelling-mismatch-induced fragmentation of physically transient electrodes is studied. The fragment size of the electrode layer as a function of initial defect distribution is investigated. The average fragment size is predicted and verified by a combination of experimental and FEM analysis. It is found that only large defects initiate fragmentation; this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…While the PEO substrate is water-soluble, printed PEDOT:PSS electrodes are not. We demonstrated in previous studies that insoluble active electrodes might undergo disintegration by swelling-induced stress of the substrate [10,[55][56][57][58]. Here, the transiency of the all-organic electrodes in water was studied and is presented in Figure 4a.…”
Section: Transiencymentioning
confidence: 84%
See 1 more Smart Citation
“…While the PEO substrate is water-soluble, printed PEDOT:PSS electrodes are not. We demonstrated in previous studies that insoluble active electrodes might undergo disintegration by swelling-induced stress of the substrate [10,[55][56][57][58]. Here, the transiency of the all-organic electrodes in water was studied and is presented in Figure 4a.…”
Section: Transiencymentioning
confidence: 84%
“…The swelling-induced stress at the interface of the PEO and the PEDOT:PSS layers was not high enough to fracture the PEDOT:PSS substrate, most probably because the modulus of the swelling PEO substrate was lower than that of PEDOT:PSS. As found in our previous analysis of interfacial stress between dissimilar materials, interfacial swelling-induced stress was highly related to the ratio of elastic modulus between swelling substrate and printed layer [55,56]. The substrate-less PEDOT:PSS electrode was then transferred onto a secondary platform for SEM imaging.…”
Section: Transiencymentioning
confidence: 88%
“…810 On the other hand, physical interfacial interaction has considerable effect on the composite properties, which is, however, usually overlooked by many researchers. 1113 Yang et al 14 reported the presence of interlocks between platelets of nacre, and the physical interaction was proved to be the key mechanism for the high toughness and strength of nacre. In this report, we first fabricated LBL assembled GO-based hybrid films using two kinds of styrenic block copolymer (SBC) resins, aiming to study the effects of both chemical and physical interfacial interactions, and to find out the key factor of improving the properties of composites with the sandwich structure.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al fabricated ultrathin PVA/GO composite films in which the existence of oxygen functional groups located on both edges and basal plane of GO and the hydroxyl groups in PVA chains makes it possible to apply LBL self-assembly by hydrogen-bonding interaction. Furthermore, the covalent bonding interaction was found in graphene-based nanocomposites. On the other hand, physical interfacial interaction has considerable effect on the composite properties, which is, however, usually overlooked by many researchers. Yang et al reported the presence of interlocks between platelets of nacre, and the physical interaction was proved to be the key mechanism for the high toughness and strength of nacre. In this report, we first fabricated LBL assembled GO-based hybrid films using two kinds of styrenic block copolymer (SBC) resins, aiming to study the effects of both chemical and physical interfacial interactions, and to find out the key factor of improving the properties of composites with the sandwich structure.…”
Section: Introductionmentioning
confidence: 99%